Capsaicin supplementation increases time to exhaustion in high-intensity intermittent exercise without modifying metabolic responses in physically active men - de Freitas, Marcelo Conrado [UNESP]; Billaut, François; Panissa, Valéria Leme Gonçalves; Rossi, Fabricio Eduardo; Figueiredo, Caique [UNESP]; Caperuto, Erico Chagas; Lira, Fabio Santos [UNESP] (Springer Nature, 2019)
Purpose: The purpose of this study was to investigate the acute effect of capsaicin supplementation on performance and physiological responses during high-intensity intermittent exercise (HIIE). Method: Thirteen physically active men (age = 24.4 ± 4.0 years; height = 176.4 ± 6.9 cm; body mass = 78.7 ± 13.8 kg; running training per week = 3.9 ± 0.9 h) performed an incremental running test to determine peak oxygen uptake (V˙ O 2Peak ) and the speed associated with V˙ O 2Peak (sV˙ O 2Peak ). Thereafter, subjects completed two randomized, double-blind HIIE (15s:15 s at 120% sV˙ O 2Peak ) trials 45-min after consuming capsaicin (12 mg) or an isocaloric placebo. Time to exhaustion, blood lactate concentration, oxygen consumption during and 20 min post-exercise, energy expenditure, time spent above 90% of V˙ O 2Peak , and the rate of perceived exertion were evaluated. Results: There was no difference between capsaicin and placebo for any variable except time to exhaustion [capsaicin: 1530 ± 515 s (102 efforts) vs placebo: 1342 ± 446 s (89 efforts); p < 0.001]. Conclusion: In conclusion, capsaicin supplementation increased time to exhaustion in high-intensity intermittent exercise without modifying the metabolic response of exercise or the rate of perceived exertion in physically active men. Capsaicin could be used to increase the training load during specific exercise training sessions.
Keywords: Energy system contribution; Excess post-oxygen consumption; Lactate